PENGARUH CITRA MEREK, KUALITAS LAYANAN DAN PERSEPSI NILAI TERHADAP LOYALITAS MEREK SERTA DAMPAKNYA PADA EKUITAS MEREK (Studi pada Mobile Phone Merek BlackBerry) - 10.42.02.0037, Achmad Safuan (Jurnal Mahasiswa Pasca Sarjana, 2013)
Human needs are always developing in accordance with the developments of technology and communication. The high number of BlackBerry users in Indonesia is an interesting phenomenon when compared to mobile phone users in developed countries. On one side consumers are not those who need BlackBerry as a push mail device, on the other hand the name of BlackBerry in Indonesia is very dominant and has very strong brand equity if it is compared to other mobile phone brands. Semarang has a relatively high number of BlackBerry users. But social fact shows that BlackBerry is only reachable for the middle to upper class segment. Thus, Chinese mobile phone manufacturers take an attitude by launching mobile phone which has the same features as BlackBerry that is Blackberry Black Market or BlackBerry BM in brief. As a follower product, it always appears the same features with the pioneer products which are often sold but it has 50% lower price. Same features and cheaper price become the mainstay for China mobile phone (BM) to cut the growth in modern mobile phone sales such as authorized BlackBerry product. In accordance with the phenomenon of declining BlackBerry sales growth, it is presumably caused by low brand loyalty and equity.The population in this study is all BlackBerry users in Semarang but the amount is not known precisely. While the samples are taken by using purposive sampling method that is sampling method based on specific criteria. This study establishes minimum criteria by coming twice and making an appointment with 3 Service Centres. This is done because the measurement of service quality has the indicators of timeliness in fulfilling the appointment with the customers. Based on the service center data there are 117 customers who had come at least twice to the BlackBerry service center.Based on the analysis that has been conducted before, this study concluded ;( 1 ) it is proven that Brand image gives positive effect on brand loyalty , it means that a better brand image will increase the brand loyalty,( 2 ) Service quality gives positive effect on brand loyalty ,it means a better service quality will increase brand loyalty, ( 3 ) Perceived value has positive effect on brand loyalty , it means the better perceived value, the better brand loyalty , and ( 4 ) brand loyalty gives positive effect on brand equity , thus, a better brand loyalty will improve the brand equit Keywords: brand image, service quality, perceived value, brand loyalty and brand equity.